2013
DOI: 10.1016/j.cyto.2013.06.309
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-independent interaction of the type I interferon receptor complex is necessary to observe its biological activity

Abstract: Ectopic coexpression of the two chains of the Type I and Type III interferon (IFN) receptor complexes (IFN-αR1 and IFN-αR2c, or IFN-λR1 and IL-10R2) yielded sensitivity to IFN-alpha or IFN-lambda in only some cells. We found that IFN-αR1 and IFN-αR2c exhibit FRET only when expressed at equivalent and low levels. Expanded clonal cell lines expressing both IFN-αR1 and IFN-αR2c were sensitive to IFN-alpha only when IFN-αR1 and IFN-αR2c exhibited FRET in the absence of human IFN-alpha. Coexpression of RACK-1 or Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The next strongest interaction is between Jak2 and IFN-γR2. We have observed that interactions between accessory chains and Janus kinases are generally of lower affinity than interactions between the ligand-binding chain and Jak1; data from the related Type I IFN receptor support this observation [25]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The next strongest interaction is between Jak2 and IFN-γR2. We have observed that interactions between accessory chains and Janus kinases are generally of lower affinity than interactions between the ligand-binding chain and Jak1; data from the related Type I IFN receptor support this observation [25]. …”
Section: Discussionmentioning
confidence: 95%
“…5D), will produce FRET efficiencies that may be artificially high, due to interactions not only between the cognate proteins but also between the donors and acceptors themselves. In fact, we found that these proteins artificially catalyzed what is normally a very weak and poor interaction between IFN-αR1 and IFN-αR2c [25]. Much of this error in FRET overestimation will be reduced if only one fluorescent protein is from jellyfish.…”
Section: Discussionmentioning
confidence: 99%
“…While originally receptor dimerization by the ligand has been proposed7, ligand-independent pre-dimerization of the receptor subunits of homodimeric class I cytokine receptors was observed891011. A similar mechanism was reported to hold true for several heterodimeric class I (refs 12, 13, 14) and class II cytokine receptors151617. Other reports suggest that ligand-independent co-clustering of receptor subunits promoted by plasma membrane microcompartmentation may support receptor assembly18192021.…”
mentioning
confidence: 86%
“…Different orientations and specific amino acid mutation at the TMD and juxtamembrane region of growth hormone and EPOR were suggested to modulate receptor dimerization and activation (21,24,25). These findings were followed by other cytokine receptors, including IL6R, EGFR, and VEGF receptor, where ligand-induced structural movements of the intracellular domains were shown to be important in signaling (26 -34), including IFNAR (35), where pre-dimerization was suggested. However, recent work has disputed the pre-formation of IFNAR1 and IFNAR2 and has shown clear evidence for ligand-induced receptor dimerization (2,36).…”
mentioning
confidence: 88%